A.L. Chism, D.J.B. Trim, and M.F. Younker. We Aim at Nothing Less Than the Whole World: The Seventh-day Adventist Missionary Enterprise and the General Conference Secretariat, 1863‒2019. Silver Spring, MD: Archives of the General Conference of Seventh-day - Wogu, Chigemezi Nnadozie (2022)
Writing Adventist history from an organizational and formal perspective is very ambitious. In general Protestant mission texts, this is a rarity. In Adventist circles, I have not come across any attempt to write a monograph about the involvement of the General Conference and its secretariat in the Christian missionary enterprise. Perhaps Barry Oliver’s magnum opus SDA Organizational Structure is the only attempt that comes close to what Chism, Trim and Younker have achieved in We Aim at Nothing Less than the Whole World. Yet even Oliver’s monograph was more about organizational changes, with the theme of mission spread sparsely in some sections of his chapters.
Keywords: Rezension